A Feminist Companion to Paul, Levine, Amy-Jill (Ed.) - Nortje, -Meyer Lilly (Neotestamentica, 2006)
This publication is the sixth volume in a new series with excellent precedent. These volumes on the texts and history of Christian origins adopt the model established by Athalya Brenner, editor of the enormously successful Feminist Companion to the Bible.